2017
DOI: 10.3389/fnagi.2017.00091
|View full text |Cite
|
Sign up to set email alerts
|

Mapping Dorsal and Ventral Caudate in Older Adults: Method and Validation

Abstract: The caudate nucleus plays important roles in cognition and affect. Depending on associated connectivity and function, the caudate can be further divided into dorsal and ventral aspects. Dorsal caudate, highly connected to dorsolateral prefrontal cortex (DLPFC), is implicated in executive function and working memory; ventral caudate, more interconnected with the limbic system, is implicated in affective functions such as pain processing. Clinically, certain brain disorders are known to differentially impact dor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
26
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(33 citation statements)
references
References 69 publications
7
26
0
Order By: Relevance
“…Activations identified when hearing to contents expressed by their partner for (a) self-condition higher than the other condition or (b) other-condition higher than the self-condition. and the ventral caudate was significantly correlated with affective functions (Huang et al, 2017). Finally, regarding the valence of the video-vignettes, in our study the neural response to positive vignettes was more evident than the response to negative vignettes.…”
Section: Discussionsupporting
confidence: 48%
See 1 more Smart Citation
“…Activations identified when hearing to contents expressed by their partner for (a) self-condition higher than the other condition or (b) other-condition higher than the self-condition. and the ventral caudate was significantly correlated with affective functions (Huang et al, 2017). Finally, regarding the valence of the video-vignettes, in our study the neural response to positive vignettes was more evident than the response to negative vignettes.…”
Section: Discussionsupporting
confidence: 48%
“…Specifically, we found a higher activation in the left ventral caudate in the self-condition when participants were watching negative vignettes. Although the role of the caudate nucleus for self-referential processing remains unclear, previous evidence has shown that the left ventral caudate region is functionally connected to the posterior insula (Di Martino et al, 2008;Huang et al, 2017), a region known for interoceptive processing and affect sharing (Craig, 2003;Singer et al, 2004). In line with this result, recent evidence has shown that the functional connectivity between the posterior insula .…”
Section: Discussionmentioning
confidence: 73%
“…In this study, we expanded upon the literature on the neural systems implicated in reward-and habit-based learning in AN by examining RSFC along the ventral (affective) to dorsal (cognitive) functional organization of the striatum (Di Martino et al, 2008;Huang et al, 2017) Exploratory analyses suggested that these abnormal patterns of connectivity might be associated with the expression of clinical symptoms in AN-R, with NAcc-SFG hypoconnectivity especially linked to cognitive eating disorder symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…The striatum is functionally organized such that more ventrally located regions, such as the nucleus accumbens (NAcc) and ventral regions of the caudate, demonstrate more limbic connectivity and greater associations with indices of reward responding (Di Martino et al, 2008; Huang et al, 2017). On the other hand, the dorsal regions of the striatum, including the dorsal caudate, are more interconnected with prefrontal regions and implicated in motor and cognitive functions, including habitual responding.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation